Ocene – Fotografski krožek / Gruppo fotografico Rečan, Fotoalbum izseljencev iz Benečije / Fotoalbum degli Emigranti della Benecia - Kodrič, Majda (Two Homelands, 1990)
This paper comprises a survey of some fundamental publications by American immigration researchers on the problem of "the second generation". Included particularly are works on the position of the second generation in the Italian and Slavic ethnic communities. The rudimentary treatments of this theme among Slovene emigrants to the USA are also considered. For practical reasons, the time rang of the surveyed American publications is somewhat limited. They reach only to the first half of the 1980$s except for some in which only a few paragraphs deal with this problem. The considered works investigate the problems of the second generation within various disciplines, such as psychology, pedagogics, historiography, social linguistic and ethnology. On the issue of the position of the second generation within the Slovene National Benefit Society, some newspaper sources were used.